Feasibility of material and media aspects of guidebook for group guidance implementation with the socratic method to increase anti-bullying awareness of middle school students - Dila Rahmawati; Suwarjo Suwarjo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
The aim of this study was to determine whether the guidance for implementing group guidance with the Socratic method to increase anti-bullying awareness of high school students meets the requirements from the material and media aspects. This research is a research and development (RnD) type which refers to the Borg development model. The data was collected using a material and media feasibility assessment sheet in the form of a scale. Assessment of the feasibility of the guide involves 2 expert lecturers. Scale data were analyzed using quantitative descriptive analysis method. The results of this study indicate that the guidebook for implementing group guidance with the Socratic method to increase anti-bullying awareness of high school students is declared very feasible both in the material and media aspects. Through these results it can be concluded that the guidebook for implementing group guidance with the Socratic method to increase anti-bullying awareness of high school students is ready to be tested on school counselor as users so that later development products are suitable for use as an alternative media for prevention bullying.